Integrating youth participatory action research and health communication to inform youth and young adult covid-19 vaccine communication research. - Kikut-Stein, Ava; Givan, Kathleen; Fishman, Jeffrey; Blanco-Liz, Ashley; Alvarez-Sanchez, David; Fletcher, Janelle; Gambrell, Raki; Hernandez, Alondra; Richardson, Ciani; Shaw, Adrianna; Oiste, James Joseph von (Health Education Research, 2024)
COVID-19 vaccination rates remain lower among adolescents compared with adults. Youth participatory action research (YPAR) offers opportunities to inform youth vaccine communication at the local and population level. However, few studies have integrated systematic health communication research with YPAR. In the current study, a diverse team of paid high school interns, undergraduate student mentors and communication researchers in West Philadelphia YPAR programs developed a theory-informed communication survey to measure teen COVID-19 vaccine beliefs, information sources and behavior. The survey was distributed locally and informed youth-created vaccine campaign messages. In addition, YPAR-derived survey measures complimented a qualitative online elicitation survey with US young adults. Responses were coded using inductive content analysis, informing measures for a subsequent population-level study of young adults. This research followed protocols approved by an Institutional Review Board. Applying a YPAR framework elevated youth voices in the study development process. Communication theory and methods aided the development of survey studies to advance both local YPAR program objectives and population-level research. Future implications are discussed.